Accuracy Evaluation of the WHO Laboratory-Based Cardiovascular Risk Chart in Predicting Cardiovascular Risk - Marlin Brigita; Purbianto; Ahmad Yani; Mulia (POLTEKKES KEMENKES PONTIANAK, 2026)
Cardiovascular disease (CVD) is the leading cause of death worldwide. The WHO Cardiovascular Risk Chart Laboratory-Based was developed as a screening tool to predict the 10-year risk of CVD events. However, its validity in Indonesia remains to be evaluated. This study aims to evaluate the accuracy of the WHO Cardiovascular Risk Chart Laboratory-Based and to analyze the relationship between risk factors such as age, gender, smoking status, systolic blood pressure, total cholesterol level, and diabetes mellitus status and the occurrence of CVD. This is a quantitative study with a retrospective cross-sectional approach using secondary data from outpatient medical records at RSUP Dr. Sitanala from January 2024 to March 2025. A total of 210 respondents were included. Data were analyzed using univariate analysis, chi-square tests, and diagnostic tests using the Receiver Operating Characteristic (ROC) curve to obtain values of AUC, sensitivity, specificity, PPV, NPV, LR⁺, LR⁻, and accuracy. A total of 107 respondents (51%) were diagnosed with CVD. The AUC value was 0.564 (p = 0.107; 95% CI: 0.487–0.642), indicating low predictive ability. Sensitivity was 66.36%, specificity 41.75%, PPV 54.2%, NPV 54.43%, LR⁺ 1.139, LR⁻ 0.806, and overall prediction accuracy was 54.3%. Significant associations were found between gender, smoking status, and total cholesterol level with the occurrence of CVD (p < 0.05). The WHO Cardiovascular Risk Chart Laboratory-Based demonstrated low predictive ability in the Indonesian cohort, different from validation in Malaysia and Sri Lanka, so local calibration is needed. Several risk factors showed significant associations with CVD occurrence.